2002
DOI: 10.1021/bi026410c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Large Peptide Fragments Derived from the N-Terminal Domain of the Ribosomal Protein L9:  Definition of the Minimum Folding Motif and Characterization of Local Electrostatic Interactions

Abstract: A set of peptides derived from the N-terminal domain of the ribosomal protein L9 (NTL9) have been characterized in an effort to define the minimum unit of this domain required to fold and to provide model peptides for the analysis of electrostatic interactions in the unfolded state. NTL9 is a 56-residue alpha-beta protein with a beta1-loop-beta2-alpha1-beta3-alpha2 topology. The beta-sheet together with the first helix comprise a simple example of a common supersecondary motif called the split beta-alpha-beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 42 publications
(62 reference statements)
3
40
0
Order By: Relevance
“…Peptide fragment studies rule out the possibility that the effects arise from a propensity for the local sequence to encode a preferred conformation which leads to a strong interaction between D8 and K12. A peptide fragment consisting of the first 22 residues of NTL9, which included the β-strand -1, loop, β strand -2 unit, was not able to fold in isolation [37] even when the N and C-termini were constrained by a Gly-Cys-CysGly linker. Constraining the fragment had only modest effects on the pK a of D8 or E17.…”
Section: Mutational Analysis Of Electrostatic Interactions In the Denmentioning
confidence: 99%
“…Peptide fragment studies rule out the possibility that the effects arise from a propensity for the local sequence to encode a preferred conformation which leads to a strong interaction between D8 and K12. A peptide fragment consisting of the first 22 residues of NTL9, which included the β-strand -1, loop, β strand -2 unit, was not able to fold in isolation [37] even when the N and C-termini were constrained by a Gly-Cys-CysGly linker. Constraining the fragment had only modest effects on the pK a of D8 or E17.…”
Section: Mutational Analysis Of Electrostatic Interactions In the Denmentioning
confidence: 99%
“…Circular dichroism and NMR-based pK a measurements were conducted on several fragment peptides of NTL9, including residues 1-11 and 1-22. It was found that even though both fragments are unstructured, the pK a of Asp 8 is shifted lower than the model value (4.0) by 0.16 and 0.34 units, respectively (13,14). Interestingly, these shifts are slightly smaller than the pK a of Asp 8 in a destabilizing mutant, V3AI4A, which was estimated to be 0.44 units (21).…”
Section: Introductionmentioning
confidence: 91%
“…We note that the unfolded states are also referred to by some workers as denatured states, since historically they were obtained using chemical denaturants or acids. The unfolded states have been traditionally thought of as random coils without preferential interactions (5,6); however, an increasing number of experimental studies point to the presence of residual structures such as the native-like topology, local and longrange order (7)(8)(9), as well as specific hydrophobic (10)(11)(12) and electrostatic interactions (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has shown that L9 is an elongated protein with a 34-residue α-helix that connects and orients the N-(NTL9) and C-terminal (CTL9) domains, which both contain a predicted RNA-binding site (Adamski et al, 1996;Lieberman et al, 2000). NTL9 is a 56-residue α-b globular protein with a b1-loop-b2-α1-b3-α2 topology (Horng et al, 2002), and CTL9 is a 92-residue α-b globular protein containing two α-helices and an unusual three-stranded mixed parallel, anti-parallel b-sheet (Hoffman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%